Relevansi Hak Asasi Manusia Dalam Perlindungan Pekerja Migran Indonesia - Hilda Alfina Rosyada; Iskandar Wibawa (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Indonesian Migrant Workers (PMI) are a vital component of the national economic structure, significantly contributing through remittances. However, behind their economic role, PMIs often face human rights violations, during placement processes, employment, and even post-employment. This article aims to examine the relevance of human rights in the protection of PMIs while highlighting the challenges and future prospects of their protection. Using a normative juridical approach and analyzing various legal instruments—such as Law No. 18 of 2017 on the Protection of Indonesian Migrant Workers, Law No. 21 of 2007 on the Eradication of Human Trafficking, and Government Regulation No. 59 of 2021 this study shows that PMI protection is not merely an administrative obligation of the state but also a constitutional duty to uphold the human rights of its citizens abroad. Judicial decisions, including Supreme Court Ruling No. 1090 K/Pid.Sus/2014 and Administrative Court Decision No. 121/G/2017/PTUN-JKT, emphasize the urgency of enforcing the principle of due diligence and effective legal protection. This article recommends strengthening oversight mechanisms, enhancing the role of foreign representatives, and integrating technology into the protection system as systematic efforts to envision a more just and humane future for Indonesian migrant workers.